Analisis Spasial Indeks Vegetasi, Suhu Permukaan dan Urban Heat Island di Kota Bogor - Demara, Raja Syahri; Nasrullah, Nizar; Budiarti, Tati (http://arl-faperta.ipb.ac.id/, 2025)
The rapid urbanisation and population growth in Bogor City has significantly decreased green open spaces from 1,982.23 ha in 2009 to 784.74 ha in 2021. This study aims to assess the extent of vegetation, land surface temperature (LST), and urban heat island (UHI) in Bogor City in 2023 spatially and develop recommendations for green open spaces development to mitigate UHI effects. Landsat 8 OLI/TIRS satellite imagery from July 20, 2023, was used to calculate the Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI), LST, and UHI intensity. The relationship between vegetation indices and LST was analyzed using RStudio to determine the required green open spaces area for reducing surface temperatures. Results showed that regions with high vegetation density had lower LST than urban areas. The UHI intensity in Bogor City was quantified by comparing urban and non urban temperatures using a 5 km buffer zone. Regression analysis revealed a significant negative correlation between vegetation indices and LST. The findings suggest that increasing green open spaces through strategic planning and development can effectively mitigate UHI effects in Bogor City, improving urban environmental quality and residents' well-being.